2017
DOI: 10.1051/0004-6361/201731023
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of the inferred transverse density profile of coronal loop threads observed with SDO/AIA

Abstract: Aims. We carry out a statistical study of the inferred coronal loop cross-sectional density profiles using extreme ultraviolet (EUV) imaging data from the Atmospheric Imaging Assembly (AIA) on board the Solar Dynamics Observatory (SDO). Methods. We analysed 233 coronal loops observed during 2015/2016. We consider three models for the density profile; the step function (model S ), the linear transition region profile (model L), and a Gaussian profile (model G). Bayesian inference is used to compare the three co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 49 publications
2
44
0
Order By: Relevance
“…The results are also consistent with the approach based on a 2D array used in Pascoe et al (2017b) and Goddard et al (2017), but the increased efficiency allows us to readily investigate the variation of the transverse density profile with time (Section 6.1).…”
Section: Forward Modeling Of Euv Intensity Profilesupporting
confidence: 75%
See 2 more Smart Citations
“…The results are also consistent with the approach based on a 2D array used in Pascoe et al (2017b) and Goddard et al (2017), but the increased efficiency allows us to readily investigate the variation of the transverse density profile with time (Section 6.1).…”
Section: Forward Modeling Of Euv Intensity Profilesupporting
confidence: 75%
“…Pascoe et al (2017b) used a similar method (applied to data from SDO/AIA) to estimate the inhomogeneous layer width of a coronal loop and found a value consistent with that calculated seismologically for the same loop in Pascoe et al (2017a). Goddard et al (2017) studied the density profiles of 233 coronal loops and found that the majority exhibit evidence for having an inhomogeneous layer of finite width. The potential for seismological techniques to provide structuring information is also relevant for studies of multi-threaded coronal structures considered by many authors (e.g., Lenz et al 1999;Aschwanden et al 2000;Pascoe et al 2007;Brooks et al 2012;Antolin et al 2015;Aschwanden & Peter 2017).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Another method for estimating ǫ is by forward modeling the appearance of the density profile for direct comparison with the transverse EUV intensity profile of the loop (Goddard et al, 2017;Pascoe et al, 2017b). It is possible to apply both of these methods simultaneously to observational data.…”
Section: Introductionmentioning
confidence: 99%
“…Observations of standing kink oscillations have recently been used to calculate the density (and Alfvén speed) profiles for coronal loops using their damping profiles by resonant absorption (Pascoe et al 2013a(Pascoe et al , 2016(Pascoe et al , 2017a(Pascoe et al , 2017c. The perpendicular inhomogeneity size has also been independently estimated by forward modeling the EUV intensity (Goddard et al 2017;Pascoe et al 2017b), although so far this has relied on the isothermal approximation (e.g., Aschwanden et al 2007), whereas hot (multi-thermal) flaring loops may require more sophisticated forward modeling (e.g., De Moortel & Bradshaw 2008;Van Doorsselaere et al 2016a). Simultaneous observations of standing kink oscillations would therefore allow the density profile to be seismologically inferred, allowing a much narrower parametric study to determine the properties of the driver (e.g., A, x D ) required to reproduce the observed wave trains and/or radio bursts.…”
mentioning
confidence: 99%